Ответы и объяснения

  • AlbuRin
  • светило науки
2013-07-26T07:07:09+04:00
(x - 2)^3 * (x + 3)^4 / ( (x^2 - 16) * (x + 5) )  > =  0
(x + 3^4  >=  0  при  любом  х.
Найдём  корни.
(x - 2)^3 = 0  ---->  x - 2 = 0,    x = 2
x^2 - 16 = 0  ---->  x_1 = -4,   x_2 = 4
x + 5 = 0  ---->  x  =  -5
Решение  неравнства  находим  методом  интервалов.
      +           -             +              -            +    ( (x-2)^3 * (x+3)^3 ) / ( (x^2-16)(x+5) ) 
-------------|----------|-----------------|-------------|---------------------------------------------
            -5        -4               2             4
Ответ.    B)     (-~ ;    -5)  U  (-4;  2]  U  (4;  +~)      ~  ----  бесконечность.